The Global Pandemic of COVID-19 as a Non-Traditional Security Threat in Indonesia - Prayuda, Rendi; Munir, Fitrisia; Jayandi, Riezki Adma; Sasmi, Dini Tiara; Suyastri, Cifebrima; Sundari, Rio (Andalas Journal of International Studies (AJIS), 2022)
The transition and development of forms of threats to the security of an international state at this time cannot always be resolved by armed forces and not only like war, this form of threat is known as non-traditional threat terms that threaten human security. The global Covid-19 pandemic not only poses a threat to aspects of national security but also has a major impact on human security. This study uses the Copenhagen perspective as the main theory in research and is supported by the concept of non-traditional security and the concept of securitization. This research method is a qualitative approach. The result shows that the global Covid-19 pandemic has provided various forms of threats to sectors on non-traditional security issues in Indonesia. The non-traditional security sectors that have received threats due to the global Covid-19 pandemic are several sectors such as Indonesian public health security, economic security, sociocultural security, etc.